Geophysical and anthropogenic drivers for global and regional fire emission trends from 2001 to 2019 - Wu, Sifeng (2022)
Fire plays an important role in the earth system. While some aspects of fire including burnt area and fire frequencies have been extensively studied; fire carbon emissions, which could exert significant influence on the carbon cycle and a wide range of geophysical processes relating to ecosystem services and human well-being, are relatively understudied in terms of its global trends and drivers. We investigated fire emission trends from 2001 to 2019 at global and regional scales using total carbon emission data from the fourth generation Global Fire Emission Database (GFED4s). We identified geophysical and anthropogenic drivers for fire emission trends for regions defined by geographical regions and biomes with a causal model; and quantified driver importance with machine learning models by estimating their impact on fire emissions. We observed an insignificant global fire emission trend; mainly caused by conflicting fire emission trends in tropical savanna/grasslands and boreal forests. The two biomes were the largest sources for global fire emissions. Tropical savanna/grasslands contributed 60% to global fire emissions and showed a decreasing fire emission trend at a rate of -9.7±1.4 ×10 12 gC/year; boreal forests contributed around 8% and increased at a rate of 7.4±2.2 × 10 12 gC/year (rates estimated by Huber robust regression). At the regional scale, we found that fire emission trends were driven by geophysical factors for all regions. Anthropogenic interventions only caused changes in fire emissions in limited regions, including all biomes in Africa, and some biomes in Boreal Asia, Central Asia and North America. Decreasing fire emission trends in tropical savanna/grasslands mainly occurred in Africa; and the most dominant drivers were anthropogenic interventions, namely agriculture expansion and the subsequent declines in vegetation. Increasing fire emissions from boreal forests largely came from Boreal Asia, where anthropogenic interventions were also important drivers, and climatic drivers relating to moisture, drought, and temperature played a vital role as well, especially moisture. Vegetation indices were also identified as drivers for this region but were the least important ones. Our results suggested future fire emission trend for boreal forests in Boreal Asia could be highly vulnerable to climate change. It is possible that fire emissions in this region continue to increase if the climate becomes drier since drivers relating to moisture were highly important. On the other hand, further decrease for fire emissions in African savanna/grasslands is limited by the already shrunk vegetation. Therefore, at the global scale, risks of increasing fire carbon emissions are rather high. Increasing carbon emissions and the slow recovery of carbon sink capacity in burnt forests imply long-term net carbon source from boreal forests, which could be challenging for climate mitigation.